(untitled) (KEMANUSIAAN The Asian Journal of Humanities, 2023)
This article aligns with the theme, “Overcoming Adversity, Embracing Change: Addressing Challenges in Language and Culture in Asia”, and with the call for papers for this conference. It takes an optimistic but critical stand on questions of digital technologies, including social media in multilingual societies. The telephone, radio, television and more recently the internet were all in their turn (wrongly) seen as heralding the demise of normal face-to-face communication, and as threatening the continued existence of minority indigenous languages in multilingual nations. But the Chinese traditional saying, “A crisis is an opportunity riding a dangerous wind”, remains relevant in the pandemic and post-pandemic era. Technologies are not in themselves language-specific, nor are they necessarily biased towards powerful, global languages. Social media platforms such as WhatsApp, Instagram and others do not force users to shift towards Spanish, Mandarin, Arabic or English. I discuss examples of mixed language use in Southeast Asian social media contexts, taking up the point raised by Deterding (2020, 175) in his article based on his keynote presentation at the previous conference in this series: “perhaps trying to analyse the different languages in Brunei as distinct entities is flawed. In the modern globalised world, languages no longer belong in distinct boxes that can be neatly labelled”. The key argument is that the mixing of local vernacular and powerful global languages does not necessarily signal an impending language shift. On the contrary, such hybrid discoursal practices in social media may be viewed as a minority language maintenance and survival strategy.